Cadaveric evaluation of canine arthroscopic bicipital tenotomy - Holsworth, I. G.; Schulz, K. S.; Ingel, K. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
The purposes of this study were to determine the optimal portal location, limb position and instrumentation for arthroscopic assisted biceps tenotomy as an alternative to open tendon transection and humeral tenodesis and to evaluate anatomical location and support of the tendon following transection.Eight canine cadaver shoulder joints underwent arthroscopic visualization of bicipital tendon length via cranio-lateral and caudo-lateral camera portals in a variety of thoracic limb positions to determine maximal tendon length visualization by anatomical marking. Comparison of tenotomy time and ease was compared between radio frequency microscalpel, blade and arthroscopic shaver. Gross anatomical dissection was performed post-tenotomy to record tendon lengths, locations and supporting structures.The cranio-lateral camera port in conjunction with combined moderate shoulder and elbow flexion optimized tendon visualization, accessible length, and instrumentation ease. Visualized tendon length varied from 39-76% of total tendon length. Tenotomy times were lowest via blade and were unable to be performed with the shaver. After tenotomy the distal tendon segment remained loosely tethered within the in- tertubercular groove at the level of the intertubercular ligament by tendon sheath and capsular attachments.Biceps tenotomy is readily performed with standard arthroscopic equipment. Appropriate limb positioning and modification of previously described portals allows maximal access. Immediately posttenotomy the distal tendon is loosely maintained within the bicipital groove by tendon sheath and capsular attachments.
Keywords: Biceps tenosynovitis; arthroscopic tenotomy; radiofrequency